PRELIMINARY QUANTIFICATION OF METAL SELENITE SOLUBILITY IN AQUEOUS SOLUTIONS - Sharmasarkar S.; Reddy K.J.; Vance G.F. (My University, 1996)
Selenium solubilization can be a potential source of environmental contamination in natural systems. Currently no experimental data are available on the solubility of metal selenites in aqueous solutions. The objective of our study was to determine the solubility of Ca, Mg, Mn, and Zn selenites. A dissolution study was conducted for 1, 2, 3, 4, 5, 10, 15, 20, 25, 30, 35 and 40 weeks with CaSeO3 . H2O, MgSeO3 MnSeO3 and ZnSeO3 . H2O using different background solutions, including distilled deionized water (DI Water), 0.01 M NaCl, 0.03 M NaCl and 0.02 M Na2SeO3. For all solids, equilibrium was reached within 40 weeks. As compared to the theoretical values obtained from literature, the experimental pK0 values for ZnSeO3 . H2O were higher, whereas for MgSeO3 the determined pK0 values were lower; theoretical and experimental data for both CaSeO3 . H2O and MnSeO3 were comparable. A comparison of the pK0 values also indicated that MgSeO3 had the highest solubility in DI water, whereas in the three other solutions MnSeO3 had the maximum solubility. The mean pK0 values determined for CaSeO3 . H2O, MgSeO3, MnSeO3 and ZnSeO3 . H2O in the above mentioned background solutions were 7.76, 7.56, 7.11, and 7.70, respectively, which indicated that the overall solubility order would be, MnSeO3 > MgSeO3 > ZnSeO3 . H2O > CaSeO3 . H2O. The results of this study are fundamental for modifying existing Se thermodynamic databases and understanding selenite solid-water interactions in natural environments.
Keywords: DISSOLUTION STUDY; SELENITE (METAL) SOLUBILITY; AQUEOUS SOLUTIONS; METAL SELENITES